Calcium hydroxide root canal sealers - Histopathologic evaluation of apical and periapical repair after endodontic treatment - Leonardo, M. R.; Silva, L. A. B.; Utrilla, L. S.; Assed, S.; Ether, S. S. (Williams & Wilkins, 1997)
Eighty root canals of the premolars of 4 dogs, with vital pulp, were instrumented and filled during the same session with the Sealapex, CRCS, Sealer 26, and Apexit sealers, the animals were sacrificed 180 days after root canal filling and their maxillae and mandibles were removed and fixed in 10% formalin, After routine histologic processing, the sections were stained with hematoxylin-eosin and Mallory trichrome, Histopathologic analysis showed that Sealapex was the sealer that best permitted the deposition of mineralized tissue at the apical level and was the only sealer that provided complete sealing (37.5% of cases), With the use of Sealapex, no inflammatory infiltrate occurred and there was no reabsorption of mineralized tissues, In contrast, partial sealing and a moderate inflammatory infiltrate occurred with the use of CRCS, When Apexit and Sealer 26 were used the absence of sealing was frequent and active reabsorption of mineralized tissues occurred in most cases, the inflammatory infiltrate predominating with the use of Apexit was of the severe type, whereas with the use of Sealer 26 the inflammatory infiltrate was mild or absent.
Keywords: Apexit; Bismuth; Calcibiotic Root Canal Sealer; Calcium hydroxide; Root canal filling material; Salicylic acid derivative; Sealapex; Sealer 26; Zinc oxide; Animal; Comparative study; Dog; Drug effect; Drug screening; Endodontics; Pathology; Periodontium; Premolar tooth; Tooth root; Animals; Bicuspid; Bismuth; Calcium Hydroxide; Dogs; Drug Evaluation, Preclinical; Periapical Tissue; Root Canal Filling Materials; Root Canal Therapy; Salicylates; Tooth Apex; Zinc Oxide